Role of Toll-like Receptors in Health and Diseases of Gastrointestinal Tract - Hadi, Najah R.; Shaker, Saad Rasool; Alharis, Nada R (Important Aspects of Toll-like Receptors: Signaling Pathways in Diseases, 2021)
The human gastrointestinal (GI) tract is colonized by non-pathogenic commensal microflora and frequently exposed to many pathogenic organisms. For the maintenance of GI homeostasis, the host must discriminate between pathogenic and non-pathogenic organisms and initiate effective and appropriate immune and inflammatory responses. Mammalian toll-like receptors (TLRs) are members of the pattern recognition receptor (PRR) family that plays a central role in the initiation of innate cellular immune responses and the subsequent adaptive immune responses to microbial pathogens. Recent studies have shown that gastrointestinal epithelial cells express almost all TLR subtypes characterized to date and that the expression and activation of TLRs in the GI tract are tightly and coordinately regulated. Initiation and perpetuation of the inflammatory intestinal responses in inflammatory bowel disease (IBD) may result from an exaggerated host defense reaction of the intestinal epithelium to endogenous luminal bacterial flora. Intestinal epithelial cell lines constitutively express several functional Toll-like receptors (TLRs) which appear to be key regulators of the innate response system. Gastric epithelial cells represent the first line of innate immune defence against H. pylori, and respond to infection by initiating numerous cell signalling cascades, resulting in cytokine induction and the subsequent recruitment of inflammatory cells to the gastric mucosa. Pathogen recognition receptors of the Toll-like receptor (TLR) family mediate many of these cell signalling events.